Noncapacitive Hysteresis in Perovskite Solar Cells at Room Temperature - Almora Rodriguez, Osbel; Aranda, Clara; Zarazua, Isaac; Guerrero, Antonio; Garcia-Belmonte, Germà (ACS Energy Letters, 2016)
The current density-voltage (J-V) curves of perovskite solar cells have a hysteresis-like distortion. Hysteresis has raised many concerns about the feasibility and long-term stability of this kind of photovoltaic technology. However, there is a lack of distinction among different hysteretic phenomena which is necessary to unravel its underlying physical and chemical mechanisms. Here we distinguish between capacitive and noncapacitive currents giving rise to specific hysteretic responses in the J-V curves of PSCs. Hysteresis dominates in regular structures with TiO2 as bottom electron selective layer. This is due to the charge, both ionic and electronic, accumulation ability of the TiO2/perovskite interface but no influence on the steady-state operation. Noncapacitive hysteresis is observable at slow enough scan rates in all kind of architectures. Inverted structures, including organic compounds as a result of the inherent reactivity of contact materials and absorbers perovskites.<br